Penerapan Model Pembelajaran Contextual Teaching And Learning dengan Pendekatan Tim Ahli Untuk Meningkatkan Hasil Belajar Siswa - Mustamu, Berthy (Jurnal Bimbingan dan Konseling Terapan, 2018)
This Study aims to determine the extent to which the application of the Contextual learning model through the material explains the process of development of Western Colonialism and Imperialism in Indonesia in Class XI IPA on 1 Christian High School in Saparua island. Method of study is School Actian Research by using descriptive qualitative approach. This Classroom Action Research (CAR) type is carried out with a three cycle strategy. In cycles 1 and 2 the results of supervision have not achieved the desired targets such as, the implementation of an innovative activities in learning process, learning tool or media, the suitable technique in applying the History materials. From the results of the learning action on cycle III, it was revealed that the improvement of the results of students’achievement of History subject through Contextual Teaching and Learning (CTL) were increased. For the average value in cycle III was 78.2 or increased of 11.35% compared to the average value of cycle II. We can concluded that based on the result observation shown that there was enough significant in improving on students’ scors result. For the History subject teachers that should adopt the CTL method concept with an expert team approach to applied the materials in classroom activities have to consider the basic competencies, content of materials, student characteristics